2003
DOI: 10.1089/10445490360708946
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Proto-Oncogene Axl in Renal Cell Carcinoma

Abstract: In this investigation, we examined the role of the Axl proto-oncogene in renal cell carcinoma (RCC). Axl is a tyrosine kinase receptor implicated in myeloid leukogenesis, and has been found to be overexpressed in lung cancers and breast cancers. Axl has been described to act as a mitogenic factor along with its ligand Gas-6. Axl has also shown to have a role in apoptosis, cell adhesion, and chemotaxis. The differential expression of the Axl RNA transcript was examined in 20 pairs of matched normal kidney and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(40 citation statements)
references
References 20 publications
1
38
0
Order By: Relevance
“…We analyzed mutant p53-induced genes for the overrepresentation of genes that contain putative p63 binding sites. The Axl gene was selected for further study based on the presence of a p63 binding site, its known role in oncogenesis, 34,40,43,46,47 and its potential role in mutant p53 GOF activities. We first verified the microarray data by performing RT-qPCR analysis of the Axl mRNA, confirming induction by mutant p53.…”
Section: Resultsmentioning
confidence: 99%
“…We analyzed mutant p53-induced genes for the overrepresentation of genes that contain putative p63 binding sites. The Axl gene was selected for further study based on the presence of a p63 binding site, its known role in oncogenesis, 34,40,43,46,47 and its potential role in mutant p53 GOF activities. We first verified the microarray data by performing RT-qPCR analysis of the Axl mRNA, confirming induction by mutant p53.…”
Section: Resultsmentioning
confidence: 99%
“…Axl overexpression has been reported in a variety of human cancers (Craven et al, 1995;Ito et al, 1999;Berclaz et al, 2001;Sun et al, 2004;Shieh et al, 2005), and is associated with invasiveness and metastasis in lung (Shieh et al, 2005), prostate (Sainaghi et al, 2005), breast (Meric et al, 2002), and gastric cancers (Wu et al, 2002) as well as in renal cell carcinoma (Chung et al, 2003) and glioblastoma (Hutterer et al, 2008). A recent study showed that Axl overexpression via a 'tyrosine kinase switch' leads to resistance to imatinib in gastrointestinal stromal tumors (Mahadevan et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Dysregulation of Axl or its ligand Gas6 is implicated in the pathogenesis of a variety of human cancers. Overexpression of Axl has been reported in a wide array of human cancers (Craven et al, 1995;Ito et al, 1999;Berclaz et al, 2001;Sun et al, 2004;Shieh et al, 2005) and is associated with invasiveness and metastasis in lung (Shieh et al, 2005), prostate (Sainaghi et al, 2005), breast (Meric et al, 2002;Zhang et al, 2008), gastric (Wu et al, 2002) and pancreatic (Koorstra et al, 2009) cancers, renal cell carcinoma (Chung et al, 2003) as well as glioblastoma (Hutterer et al, 2008). Recently, by profiling of phosphotyrosine signaling, activated Axl protein was detected in about 5% primary tumors of non-small-cell lung cancer (NSCLC) (Rikova et al, 2007).…”
Section: Introductionmentioning
confidence: 99%